Experimental investigation on the blocking of groundwater seepage from a waterproof curtain during pumped dewatering in an excavation - Xu, Ye-Shuang; Yan, Xue-Xin; Shen, Shui-Long; Zhou, An-Nan (Hydrogeology journal, 2019)
The interaction between a waterproof curtain and withdrawal wells (or simply, the wall-well effect) is a key factor in controlling the environmental effects that occur during the dewatering of foundation pits. A series of laboratory investigations was conducted to study the changes in groundwater level during dewatering. The influence of the buried depth of the waterproof curtain placed in a dewatering confined aquifer ( D ), and the filter length of the pumping well ( L ), is investigated. Based on the laboratory test results, numerical simulations are used to analyse the ground settlement. The relationship between the approximate hydraulic gradients on both sides of the wall (Δ i ), or the ground settlement outside the excavation ( S ), using ratio R D ( D divided by the thickness of the confined aquifer) or ratio R L ( L divided by the thickness of the confined aquifer), can be simulated using a Boltzmann curve. The value of Δ i increases while S decreases with an increase in R D , whereas Δ i decreases while S increases with an increase in R L . The value of the contraflexure point of the Boltzmann curve is regarded as the effective value of R D or R L . Based on a comprehensive consideration, R D is suggested to be equal to or larger than the effective value, and R L is suggested to be equal to or lesser than the effective value.